Design and optimization of a micro capacitive pressure sensor - Tahmasebpour, Kamyar; Shobaki, Mohammed M.; Hrairi, Meftah (2013)
The shape of Micropressure sensors has influence on their accuracy. In this paper, a rectangular membrane type Micropressure sensor had been modeled using finite element package and shape optimization in order to design a more accurate flexible membrane. The results show that adding a slim wall, to protect the pressure sensor and system during pressure shocks, has a negligible effect on the membrane flexibility. Moreover, the simulation results show that the sensor exhibits a linear response with wide range of pressure from 0.01 MPa to 70 MPa. Furthermore, the simulation results yielded that the load-deflection responses could be enhanced using a spacer.